The New Runner's High? Examining Relationships Between Cannabis Use and Exercise Behavior in States With Legalized Cannabis - YorkWilliams, Sophie L.; Gust, Charleen J.; Mueller, Raeghan; Bidwell, L. Cinnamon; Hutchison, Kent E.; Gillman, Arielle S.; Bryan, Angela D. (Frontiers in Public Health, 2019)
Scientific literature examining cannabis use in context of health behaviors, such as exercise engagement, is extremely sparse and has yielded inconsistent findings. This issue is becoming increasingly relevant as cannabis legalization continues, a situation that has been associated with increased initiation of use among adults, and increased potency of available products in legalized states. Physical activity is among the most important health behaviors, but many Americans do not meet minimum exercise recommendations for healthy living. Common issues surrounding low exercise rates include inadequate enjoyment of and motivation to exercise, and poor recovery from exercise. It is unclear whether cannabis use shortly before and/or after exercise impacts these issues, and whether this co-use affects exercise performance. The present online survey study examines attitudes and behaviors regarding cannabis use with exercise among adult cannabis users living in states with full legal access (N=605). Results indicated that the majority (81.7%) of participants endorsed using cannabis concurrently with exercise, and those who did tended to be younger and more likely to be males (p<0.0005 for both). Even after controlling for these differences, co-users reported engaging in more minutes of aerobic and anaerobic exercise per week (p<0.01 and p<0.05, respectively). In addition, the majority of participants who endorsed using cannabis shortly before/after exercise reported that doing so enhances their enjoyment of and recovery from exercise, and approximately half reported that it increases their motivation to exercise. This study represents an important step in clarifying cannabis use with exercise among adult users in states with legal cannabis markets, and provides guidance for future research directions.